PERLINDUNGAN HAK EKONOMI PEMEGANG HAK CIPTA ATAS LAGU MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Plumbantoruan, Christopher Khoirun; Saidin, Saidin Purnamasari; Runtung, Runtung Purnamasari (Smart Education, 2025)
Abstract: The Indonesian music industry continues to grow, creating economic opportunities for songwriters and copyright holders. However, advances in technology and easy access to musical works also pose challenges in protecting the economic rights of creators. Law Number 28 of 2014 concerning Copyright (UUHC) exists as the government's effort to strengthen copyright protection, including the economic rights of copyright holders for songs. The problems in this research are what are the conditions and procedures for obtaining permission to perform songs from copyright holders, what is the authority of collective management institutions in granting permits to perform songs written by other people, and what is the mechanism for resolving civil disputes related to the use of the copyright holder's economic rights to songs? according to Law no. 28 of 2014.Keyword: Protection of Economic Rights, Copyright Holders, Songs Abstrak: Industri musik Indonesia terus berkembang, menciptakan peluang ekonomi bagi pencipta lagu dan pemegang hak cipta. Namun, kemajuan teknologi dan kemudahan akses terhadap karya musik juga menimbulkan tantangan dalam melindungi hak ekonomi pencipta. Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta (UUHC) hadir sebagai upaya pemerintah untuk memperkuat perlindungan hak cipta, termasuk hak ekonomi pemegang hak cipta atas lagu. Permasalahan dalam penelitian ini yaitu bagaimana syarat-syarat dan prosedur untuk mendapatkan izin membawakan lagu dari pemegang hak cipta, bagaimana kewenangan lembaga manajemen kolektif dalam pemberian izin membawakan lagu ciptaan orang lain, serta agaimana mekanisme penyelesaian sengketa perdata terkait pemanfaatan hak ekonomi pemegang hak cipta atas lagu menurut UU No. 28 Tahun 2014.Kata kunci: Perlindungan Hak Ekonomi, Pemegang Hak Cipta, Lagu